Real democracy - "Bryan, Frank M." (Chicago, 2004)
Can ordinary people really gather together and make laws that are binding on themselves and their communities? Frank M. Bryan discusses this with particular reference to the New England town meeting which provides a model of such a pure form of democracy.
Keywords: Local government-New England